Analysis of Iron and Iron-Interacting Protein Dynamics During T-Cell Activation - Teh, Megan R.; Frost, Joe N.; Armitage, Andrew E.; Drakesmith, Hal (Frontiers in Immunology, 2021)
Recent findings have shown that iron is a powerful regulator of immune responses, which is of broad importance because iron deficiency is highly prevalent worldwide. However, the underlying reasons of why iron is needed by lymphocytes remain unclear. Using a combination of mathematical modelling, bioinformatic analysis and experimental work, we studied how iron influences T-cells. We identified iron-interacting proteins in CD4+ and CD8+ T-cell proteomes that were differentially expressed during activation, suggesting that pathways enriched with such proteins, including histone demethylation, may be impaired by iron deficiency. Consistent with this, iron-starved Th17 cells showed elevated expression of the repressive histone mark H3K27me3 and displayed reduced RORγt and IL-17a, highlighting a previously unappreciated role for iron in T-cell differentiation. Quantitatively, we estimated T-cell iron content and calculated that T-cell iron demand rapidly and substantially increases after activation. We modelled that these increased requirements will not be met during clinically defined iron deficiency, indicating that normalizing serum iron may benefit adaptive immunity. Conversely, modelling predicted that excess serum iron would not enhance CD8+ T-cell responses, which we confirmed by immunising inducible hepcidin knock-out mice that have very high serum iron concentrations. Therefore, iron deficiency impairs multiple aspects of T-cell responses, while iron overload likely has milder effects.